Paths and rivers. Sa’dan Toraja society in transformation - Schouten, Maria Johanna Christina (2010)
Review of major monograoh about the Sa´dan Toraja, an ethnic group in Central Sulawesi, Indonesia. The Sa’dan Toraja, wet-rice cultivators living in the highlands of South Sulawesi, are among the best-known ethnic groups of Indonesia. Their elaborate rituals, grandiose ancestral houses and intriguing artistic expressions attract the interest of foreign and domestic tourists, and anthropologists and historians have attested to the richness and the dynamics of Toraja culture in its many local variations. [...]